MARTIAL ART AUGMENTED REALITY BOOK (ARBOOK) SEBAGAI MEDIA PEMBELAJARAN SENI BELADIRI NUSANTARA PENCAK SILAT - Adi Sucipto; Qadli Jafar Adrian; Muhammad Agie Kencono (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Pencak silat is one of the archipelago cultures that must be preserved. Many people want to learn silat. Fighters need a good memory in practicing, to remember every silat movement. This must be done repeatedly to understand. For independent study, the only media available are manual books and no teaching aids. This causes the fighter to experience difficulties. Based on these problems, a medium is needed as a prop that can help fighters remember silat movements. To solve this problem, this research will make a learning media using augmented reality-based silat movement guide book (ARBook). This learning media serves as a guide to basic silat movements in the form of Android-based 3D animation visualization, with the aim of being a martial arts props. This makes this method better than the conventional manual method. Based on the results of alpha testing using a black box. So from these data, it can be seen that the 3D AR pencak silat motion application runs and in accordance with the specified functionality are included in the feasible category. In Beta testing that uses the acceptance method, 86% of respondents agree that the AR 3D Silat Motion Application is very useful, then 87% of respondents agree that it is easy to use, then 84% of respondents agree that the animated content is presented, and 79% of respondents are interested in using the Motion Application AR 3D Silat. Suppose calculated to have an average value of 84%. So it can be concluded that the value of 84% is included in the "Very Appropriate" category. Broadly speaking, Alpha and Beta testing shows that this application is considered very feasible and usable.